DEVELOPING LEADERSHIP QUALITIES OF PRESCHOOL CHILDREN THROUGH THE STEAM APPROACH (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article examines the potential of the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach in developing leadership qualities among preschool children. It highlights how collaborative, creative, and project-based learning within STEAM fosters initiative, decision-making, responsibility, and communication skills. By integrating science, technology, engineering, arts, and mathematics in playful and age-appropriate forms, preschool educators can nurture children’s leadership abilities alongside cognitive, social, and emotional growth. The study emphasizes the importance of teacher facilitation, cultural responsiveness, and innovative practices in ensuring the effective application of STEAM for early leadership development.